54. Early neurophysiological signs of disease in SOD1G93A mouse model: A stimulated single-fiber electromyography study. Issue 12 (December 2016) - Bianchi, F.; Rossi, C.; Muzio, L.; Riva, N.; Butera, C.; Cursi, M.; Amadio, S.; Comi, G.; Quattrini, A.; Carro, U. Del
Abstract : Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by a progressive degeneration of the corticospinal tract motor neurons. Growing evidence, especially derived from studies in murine models, could suggest that ALS is a distal axonopathy in which axonal degeneration occurs early during the disease, preceding the degeneration of motoneuron soma in the ventral horn of the spinal cord and the onset of symptoms (Fischer et al., 2004; Dadon-Nachum et al., 2011). A combination of molecular and subcellular events, such as protein misfolding, oxidative damage, mitochondrial alterations, impairment of glutamate transmission leading to excitotoxicity, and axonal transport impairment has been implicated in motoneuron vulnerability in ALS (Ferraiuolo et al., 2011). These observations led to consider the neuromuscular junction (NMJ) as a major player in the initiation and progression of ALS. Aim of this study was to investigate the functionality of the NMJ through all the course of the disease in the hSOD1G93A ALS mouse model, by means of single-fiber electromyography (SFEMG) technique. A comprehensive neurophysiological investigation (including sciatic nerve conduction, MEPs by transcranial electrical stimulation and sSFEMG) was carried out on 5 WT and 5 hSOD1G93A mice, at different time-points (50-70-90-110 ± 3 PND). In the early pre-symptomatic phase (50 PND), hSOD1G93A mice presented a significant jitter elongation [MCD (mean ± SE): 18.36 ± 3.21 in hSOD1G93A, 8.23 ± 0.84 in WT; p 0.021] together with increased fiber density [FD (mean ± SE): 1.62 ± 0.17 in hSOD1G93A, 1.27 ± 0.10 in WT; p 0.117] when compared with controls, suggestive of recent reinnervation process. No difference were found in peripheral conduction and MEPs parameters at the same time-point. Our results show that the neuromuscular transmission of hSOD1G93A mice is altered since the early presymptomatic phase of the disease. This probably derive from an early denervation-reinnervation process resulting in immature collateral nerve terminals and instability of neuromuscular transmission. SFEMG seems to be more sensitive in detecting the early signs of the disease compared to the other neurophysiological techniques, and could be a valuable tool for monitoring the effectiveness of new experimental therapeutic approach.